LEGAL CONSEQUENCES OF DELAY REPORTING OF SHARE ACQUISITION BETWEEN PT. AGRO PRATAMA AND PT. DHARMA SATYA NUSANTARA BASED ON LAW NUMBER 5 OF 1999 CONCERNING PROHIBITION OF MONOPOLY PRACTICES AND UNFAIR BUSINESS COMPETITION (KPPU Case Study Number 29/KPPU-M - Annisa Putri azra; Anwar Hidayat; Yuniar Rahmatiar (Justisi: Jurnal Ilmu Hukum, 2023)
The acquisition of a company is a legal act carried out by a legal entity or an individual to take over the shares of a company by purchasing a portion or the entire wealth of the company. The problem identified in this research is why reporting of company share acquisitions to the Commission for the Supervision of Business Competition (KPPU) is only related to acquisitions that have material value and what are the legal consequences of the delay in acquiring company shares in Case Number 29/KPPU-M/2019. The purpose of this research is to understand the reasons why reporting of company share acquisitions to the KPPU is only related to acquisitions that have material value and to determine the legal consequences of the delay in acquiring company shares in Case Number 29/KPPU-M/2019. This research uses a normative juridical approach. The data collection technique used in this research is literature study using primary legal materials and secondary legal materials as data sources. In conclusion, the rules regarding non-material reporting are not explicitly stated in KPPU Regulation Number 1 of 2009 concerning Pre-Notification, Mergers, Consolidations, Acquisitions, and Takeovers. As for the alleged delay in reporting in the acquisition of the company, PT. Dharma Satya Nusantara is required to pay an administrative fine as a consequence of the delayed reporting, as stipulated in Article 29(1) of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition.